2011
DOI: 10.1111/j.1365-3040.2011.02446.x
|View full text |Cite
|
Sign up to set email alerts
|

A molecular framework for the inhibition of Arabidopsis root growth in response to boron toxicity

Abstract: Boron is an essential micronutrient for plants and is taken up in the form of boric acid (BA). Despite this, a high BA concentration is toxic for the plants, inhibiting root growth and is thus a significant problem in semi-arid areas in the world. In this work, we report the molecular basis for the inhibition of root growth caused by boron. We show that application of BA reduces the size of root meristems, correlating with the inhibition of root growth. The decrease in meristem size is caused by a reduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 67 publications
3
57
0
2
Order By: Relevance
“…5e-h, B-toxicity resulted in the death of epidermal cells in root elongating and mature zones, which are involved in mineral nutrition absorption, and hence resulted in growth inhibition of the plants. However, Aquea et al (2012) showed that B-toxicity decreased Arabidopsis root meristem size and cell production rate, thus inhibiting root growth.…”
Section: B Absorption and Accumulation In Plantsmentioning
confidence: 97%
See 1 more Smart Citation
“…5e-h, B-toxicity resulted in the death of epidermal cells in root elongating and mature zones, which are involved in mineral nutrition absorption, and hence resulted in growth inhibition of the plants. However, Aquea et al (2012) showed that B-toxicity decreased Arabidopsis root meristem size and cell production rate, thus inhibiting root growth.…”
Section: B Absorption and Accumulation In Plantsmentioning
confidence: 97%
“…Although B-toxicity to plants has long been recognized (Christensen 1934), the mechanism by which B is toxic to plants is poorly understood yet (Nuttall 2000;Ruiz et al 2003;Reid et al 2004) except for the demonstrated effects of B-toxicityinduced increase in reactive oxygen species (ROS) in tobacco (García et al 2001), tomato (Cervilla et al 2007(Cervilla et al , 2009) and chickpea (Ardic et al 2009). Recently, Aquea et al (2012) reported the molecular basis for the inhibition of root growth caused by B-toxicity in Arabidopsis. They observed that B-toxicity induced the expression of genes involved in ABA signaling, ABA response and cell wall modifications, and repressed the expression of genes encoding water transporters, concluding that B-toxicity triggered a water-stress response associated with root growth inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Such communication has been shown to occur via auxin-abscisic acid-ethylene cross-talks in poplars (Popko et al 2010). However, recent findings indicate that auxin is not involved in B toxicity signaling in Arabidopsis and the main signaling mechanism for B toxicity seems to be abscisic acid, which triggers root growth inhibition via a hydric stress response (Aquea et al 2011). Although, NR has been applied for root growth investigations in various studies (Menon et al 2007b;Moradi et al 2009a), a quantitative comparison of the NR detectable root length and the real length of the root system was unavailable yet.…”
Section: Discussionmentioning
confidence: 99%
“…O crescimento radicular é utilizado como indicativo do comportamento de plantas submetidas a diferentes estresses (AQUEA et al, 2012;CHO et al, 2011;PAVLOVKIN et al, 2009) provavelmente estaria agindo sobre a parede, as evidências apontam para uma possível ação do Ca 2+ sobre a parede celular para impedir a formação de danos, evitando assim a elevação da atividade enzimática (APÊNDICE B).…”
Section: Atuação Do Cálcio No Alívio Da Acidez E Toxidez Por Alumíniounclassified
“…O boro é um elemento essencial para formação da parede celular (BLEVINS; LUKASZEWSKI, 1998;BROWN et al, 2002;HU, 1997) e existem diversos estudos sobre os efeitos de sua deficiência (CAKMAK; RÖMHELD, 1997;GUPTA et al, 1985;KUMAZAWA, 1975KUMAZAWA, , 1976aKUMAZAWA, , 1976b ou sobre a toxidez quando em excesso (AQUEA et al, 2012;DÍAZ et al, 2011;DURSUN et al, 2010;NABLE;PAULL, 1997;REID et al, 2004 Apêndice B: Tabela de ANOVA para correlação entre atividade guaiacol peroxidase (GPOX) após 8 h de exposição e absorção de azul de Evan's após 6 h de exposição, utilizando os tratamentos com 0,5 mM e 10 mM de CaCl 2 , em pH 5,8, 4,5, e 4,0 na presença de 10 µM de AlCl 3 ou em sua ausência. (n=20).…”
Section: Boro Protege As Raízes Contra a Perda Na Viabilidade E Induçunclassified